Core-brominated tetraazaperopyrenes as n-channel semiconductors for organic complementary circuits on flexible substrates - Geib, Sonja; Zschieschang, Ute; Gsänger, Marcel; Stolte, Matthias; Würthner, Frank; Wadepohl, Hubert; Klauk, Hagen; Gade, Lutz H. (Advanced functional materials, 2013)
Organic thin-film transistors (TFTs) are prepared by vacuum deposition and solution shearing of 2,9-bis(perfluoroalkyl)-substituted tetraazaperopyrenes (TAPPs) with bromine substituents at the aromatic core. The TAPP derivatives are synthesized by reacting known unsubstituted TAPPs with bromine in fuming sulphuric acid, and their electrochemical properties are studied in detail by cyclic voltammetry and modelled with density functional theory (DFT) methods. Lowest unoccupied molecular orbital (LUMO) energies and electron affinities indicate that the core-brominated TAPPs should exhibit n-channel semiconducting properties. Current-voltage characteristics of the TFTs established electron mobilities of up to μn = 0.032 cm2 V−1 s−1 for a derivative which was subsequently processed in the fabrication of a complementary ring oscillator on a flexible plastic substrate (PEN).
Gesehen am 03.02.2020